A Novel Stability Analysis of Uncertain Switched Systems with Time-Varying Delays. (10th June 2015) - Huang, Ganji; Luo, Shixian; Wei, Linna; Chen, Wuhua
Abstract : This paper deals with the stability of switched systems with time-varying delay. The time-varying system parameters are assumed to be norm-bounded. Based on a novel switched time-varying Lyapunov functional method, some new LMI-based sufficient conditions have been obtained to ensure the exponential stability for the uncertain switched delays systems. Finally, the proposed method is applied to a numerical example and the simulative results are also given.